Conservative management of grade 5 renal injury: Case report - Abdirahman Burale; Elias Sertse; Solomon Bishaw; Ferid A. Abubeker; Musse Ahmed; Samatar Abshir Mohamed; Hassan Sh Abdirahman Elmi (Urology Case Reports)
Blunt trauma is a common cause of renal injuries, usually managed conservatively unless there's hemodynamic instability, which warrants surgery. We present a case of a 22-year-old male with isolated Grade 5 renal injury, diagnosed via CT scan after blunt trauma. Despite the severity, he was successfully treated without surgery through conservative management in the ICU, with frequent monitoring and stabilization of his condition. While the best approach for hemodynamically stable Grade 5 renal injuries remains debated, our case suggests that conservative management is a viable option when patients are carefully monitored for any signs of instability.